RANCANGAN SISTEM INFORMASI MONITORING PERSEDIAAN BAHAN BAKU PRODUKSI - Heru Winarno; Luluk Harjanto; Sarah Fianti (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
Production of raw materials is one of the scopes of PT. Cahaya Harapan Satya has a direct impact on production performance. Delays in the fulfillment of product orders ordered by consumers can harm the company. Meanwhile, if the supply of raw materials is excessive, it can increase storage costs, damage, and loss of raw materials. The purpose of this study is to overcome existing problems, for that, it is necessary to make an inventory system application that is useful for monitoring the availability of web-based production raw materials to solve the problems that occur. The web-based production raw material inventory data processing system that has been created is expected to be applied properly so that it can minimize and even solve problems that previously often occurred